2008
DOI: 10.1021/ac800747q
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Cytokines Enabled by Nanoscale ZnO Arrays

Abstract: Early detection of disease markers can provide higher diagnostic power and improve disease prognosis. We demonstrate the use of zinc oxide nanorod (ZnO NR) arrays in a straightforward, reliable, and ultrasensitive detection of the cytokines interleukin-18 and tumor necrosis factor-alpha. Specifically, we exploit the fluorescence-enhancing properties of ZnO NR platforms in cytokine assays involving both a pure buffer and urine. The detection sensitivity achieved using this ZnO NR method is in the subfemtogram p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 51 publications
0
87
0
Order By: Relevance
“…8,9,4856 Specifically, this review will focus on the recent development of one-dimensional (1D) ZnO in fluorescence-based in vitro biodetection. Fluorescence is one of the most widely used detection mechanisms in many fields such as biology, biophysics, biochemistry, genomics, proteomics, drug discovery, disease diagnostics and environmental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,4856 Specifically, this review will focus on the recent development of one-dimensional (1D) ZnO in fluorescence-based in vitro biodetection. Fluorescence is one of the most widely used detection mechanisms in many fields such as biology, biophysics, biochemistry, genomics, proteomics, drug discovery, disease diagnostics and environmental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, zinc oxide (ZnO) is an extremely versatile material even at the nanoscale, due to processing through many synthetic routes [3], easy integration into periodically patterned nanoplatforms [4][5][6], desirable optical properties [7] and stability in typical biomolecular detection environments [8]. Moreover, nanostructured ZnO materials possess high surface area and good biocompatibility and biodegradability [9] that make them very advantageous as platforms to detect the immobilization of glucose [10], cholesterol [11], DNA [5,12] and several other biomolecules [13][14][15][16]. In particular, examples of the use of nanoscale ZnO in the enhanced fluorescence detection of protein interactions have shown that ZnO can act as an excellent signal-intensifying substrate for a wide range of biomolecules [1,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nanostructured ZnO materials possess high surface area and good biocompatibility and biodegradability [9] that make them very advantageous as platforms to detect the immobilization of glucose [10], cholesterol [11], DNA [5,12] and several other biomolecules [13][14][15][16]. In particular, examples of the use of nanoscale ZnO in the enhanced fluorescence detection of protein interactions have shown that ZnO can act as an excellent signal-intensifying substrate for a wide range of biomolecules [1,17,18]. Recently, the ultra-sensitivity of zinc oxide nanorod arrays in conjunction with a FITC-labeled affinity peptide has been successfully demonstrated for biosensing applications [19].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO nanorod, an economical metal oxide, demonstrates strong fluorescence-enhancing ability for neighboring fluorophores due to its intriguing optical properties (Adalsteinsson et al, 2008;Dorfman et al, 2006a,b;Hu et al, 2010a;Kumar et al, 2006). Moreover, unlike on the metallic surfaces, the enhancement is robust without quenching risk even if the fluorophores are directly 0956-5663/$ -see front matter © 2011 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%